Perancangan Proyek Ritel Butik dengan Pendekatan Sense of Place oleh Konsultan Arsitektur Interior Espace Normal - Christofaro, Veni Marcellia; Wardhani, Dyah Kusuma (Universitas Ciputra Surabaya, 2024)
This project is entitled “Boutique Retail Project Design with an In-Depth Sense of Place by Espace Normal Interior Architecture Consultants” on Argopuro Boulevard Street, Jember, East Java. Boutique retail design with a sense of place aims to create a unique and memorable shopping experience through design elements that strengthen customers' emotional attachment to space and preserve the culture in Indonesia, considering that technology in this modern era can shift the original culture of society. Sense of place here describes the emotional ties and meaning that individuals feel towards a place so that it becomes the key to forming a boutique identity and being different from other boutiques. The design methodology includes observation, interviews, literature study, typology study, and design concept development. As for the design concept, this design will later apply one of the themes from JFC (Jember Fashion Carnival), namely